IMPLIKASI HUKUM PERSETUJUAN GENERAL AGREEMENT ON TRADE IN SERVICES (GATS) – WORLD TRADE ORGANIZATION (WTO) TERHADAP PENGATURAN KEPARIWISATAAN DI INDONESIA - Satya Mahayani, Putu Ayu; Sujana, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
Through Regulation Number 7, Year 1994, Indonesia has ratified WTO Agreement. GATS is part of WTO Agreement and is located in Annex IB of the Agreement. GATS-WTO that is multilateral ties binds Indonesia. The Agreement of GATS-WTO has implication of law in which Indonesia must adapt all rules in tourism towards rules and principles of GATS-WTO. Indonesia must also announce regulations made by the Government having effects in the performance of GATS.
Keywords: Law Implication, General Agreement On Trade in Services (GATS) World Trade Organization (WTO) Agreement, Tourism Organization